2023
DOI: 10.1039/d3gc02075d
|View full text |Cite
|
Sign up to set email alerts
|

l-Lysine-induced green synthesis of CoS/Co3O4 nanoframes for efficient electrocatalytic oxygen evolution

Abstract: The Co-based heterojunction is regarded as one of the efficient materials for oxygen evolution reaction (OER), but the synthesis is still faced with time- and labor-consuming, and environmentally unfriendly. Herein,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The two dominant binding energy peaks at 781.5 and 798.0 eV originate from the Co 3+ , and two dominant binding energy peaks at 784.2 and 800.5 eV can be attributed to the Co 2+ . It is noteworthy that the Co 3+ and Co 2+ binding energy peaks of Co/Co 3 O 4 @NC have positively shifted by ∼0.8 eV compared with those of Co–Co 3 O 4 @NC, which indicates that the formation of Co/Co 3 O 4 heterojunction caused the change in the electronic structure of Co 3 O 4 . It has been shown that due to the difference in charge density in the Co/Co 3 O 4 heterostructure, the strong electron absorption ability of the O atom in Co 3 O 4 leads to the spontaneous charge flow of the adjacent zerovalent metal Co atom to Co 3 O 4 . , In addition, according to the area ratio of the fitting peak at XPS Co 2p, it can be roughly estimated that the ratio of Co to Co 3 O 4 in Co/Co 3 O 4 @NC was about 3:10. The XPS C 1s of Co/Co 3 O 4 @NC is also deconvolved into three major peaks, including the C–C bond, C–N/C–O bond, and CO bond. , The presence of a C–N bond also indicates that N has entered the lattice of carbon (Figure S6).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The two dominant binding energy peaks at 781.5 and 798.0 eV originate from the Co 3+ , and two dominant binding energy peaks at 784.2 and 800.5 eV can be attributed to the Co 2+ . It is noteworthy that the Co 3+ and Co 2+ binding energy peaks of Co/Co 3 O 4 @NC have positively shifted by ∼0.8 eV compared with those of Co–Co 3 O 4 @NC, which indicates that the formation of Co/Co 3 O 4 heterojunction caused the change in the electronic structure of Co 3 O 4 . It has been shown that due to the difference in charge density in the Co/Co 3 O 4 heterostructure, the strong electron absorption ability of the O atom in Co 3 O 4 leads to the spontaneous charge flow of the adjacent zerovalent metal Co atom to Co 3 O 4 . , In addition, according to the area ratio of the fitting peak at XPS Co 2p, it can be roughly estimated that the ratio of Co to Co 3 O 4 in Co/Co 3 O 4 @NC was about 3:10. The XPS C 1s of Co/Co 3 O 4 @NC is also deconvolved into three major peaks, including the C–C bond, C–N/C–O bond, and CO bond. , The presence of a C–N bond also indicates that N has entered the lattice of carbon (Figure S6).…”
Section: Resultsmentioning
confidence: 92%
“…The active site of the catalyst with Co/Co 3 O 4 heterojunction has been proved by the previous study, and the electrons will spontaneously transfer from the Co side to the Co 3 O 4 side across the Co/Co 3 O 4 interface upon direct contact, until the Fermi levels on both sides reach equilibrium. 23,26 Therefore, the catalytic active sites for OER and ORR tend to be on the Co site at the Co/Co 3 O 4 heterojunction interface. 22,25 Based on the above results, Co/ Co 3 O 4 @NC as a bifunctional catalyst does show many advantages in alkaline media.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxygen evolution reaction (OER) plays a fundamental and important role in clean energy conversion devices, 1 such as water splitting [2][3][4] and metal-air batteries. 5,6 However, the conversion efficiency of these devices heavily suffers from the sluggish reaction kinetics and complex reaction pathways of the OER.…”
Section: Introductionmentioning
confidence: 99%